Essential Elements for a GMP Analytical Chemistry Department. - Catalano, Thomas (Springer, 2013)
Essential Elements for a GMP Analytical Chemistry Department is a systematic approach to understanding the essential elements required for a successful GMP Analytical Department to function as an efficient and effective organization. It describes in detail a department structure which allows for the necessary processes to become available to all its personnel in a way where there is a free flow of information and interaction. The environment and culture created by this approach encourages and rewards the sharing of ideas, skills, and abilities among department personnel. The essential element.